Objetivo de leitura: um caminho que se perdeu? - Tâmara Lyz Milhomem de Oliveira (2018)
Since the multifaceted constitution of the reading process (COSCARELLI, 1999; GOODMAN, 1967, 1971; LEFFA, 1999; SMITH, [1989] 2003) and considering some of its various constituents and dimensions, we aim to develop in this work, a study focused in the aspects that supports it, the purpose of reading. Our intention is to realize if the specificities of different reading environments have influenced the accomplishing of its goal. For this undertaking, we start a theoretical path that involved the outlines of reading (COSCARELLI, 1999; MOITA LOPES, 1996; SILVEIRA, 2005; GIBSON, 1985; SOARES, 2000; DELLISOLA, 1988; SNOW 2002; CAFIERO, 2005; SCHARDOSIM, 2015; KLEIMAN 1997, 2002, 2004, 2012), it was increased for the discussions around reading performances in multiple sources (AZEVEDO, 2013; COIRO, 2011; COSCARELLI e COIRO 2014, KINGSLEY e TANCOCK, 2014; RIBEIRO, 2009) and it deals with features and issues related to textual materialities and research spaces embedded in our work, related to the digital and the printing (COSCARELLI 2006; RIBEIRO 2009; XAVIER 2004). Regarding this first research step, we used questionnaires and designed reading and research profiles of a big group of subjects, composed by 394 students of a public university. After that, we replicated the experience forwarding it to the observed subjects in this study 34 students of two public teaching institutions. Then, we turned to this investigation observation phase, in which we registered the interaction of these last subjects with texts in different environments: library (reading space of written text) and lab (reading space of digital texts). A practice that had as an aim to verify the relation between the specifities of these spaces and its texts (hipertextuality, mutiplicity of modes, lack of coexistence with searches in the library, exposure to texts of different levels and areas) and the achievement of the reading pruprose. In the last phase of analysis, we evaluate the texts produced by the subjects as result of the searches for information and readings observed in this research. The results obtained by this described work have evidenced the coadjuvant role of the research environment and reading facing the subjects development for the accomplishing of an effective search and communication of the found information. In other words, the relative variable to the reading environment was not decisive, exclusively, for the satisfactory results of reading in multiple sources. Key-words: Reading purpose. Written text. Digital hipertext. Reading. Research.